FCGR1A Serves as a Novel Biomarker and Correlates With Immune Infiltration in Four Cancer Types - Xu, Ji-li; Guo, Yong (Frontiers in Molecular Biosciences, 2020)
Background: FCGR1A encodes a protein that plays an important role in the immune response. The prognosis and tumor immune infiltration of FCGR1A in heterogeneous tumors remains unclear. Methods: Differential expression analysis of FCGR1A between tumor and normal tissues and the difference in overall survival (OS) among different cancer types were performed by Gene Expression Profiling Interactive Analysis (GEPIA). The correlation between FCGR1A and cancer immune infiltration or immue gene markers was completed through Tumor Immune Estimation Resource (TIMER) site. Results: FCGR1A exhibited high expression in various cancer types. FCGR1A was significantly correlated with the overall survival (OS) of cervical and endocervical cancer (CESC), cholangiocarcinoma (CHOL), kidney renal clear cell carcinoma (KIRC) and skin cutaneous melanoma (SKCM) (P<.05). High expression of FCGR1A meant a better prognosis except for KIRC. FCGR1A showed significant differences at different stages of KIRC and SKCM (P<.05). Furthermore, FCGR1A was notably associated with immune infiltrating levels of CD4+ T cell, CD8+ T cell, B cell, macrophage, neutrophil, and dendritic cell in the four cancers (P<.05). FCGR1A also showed close relevance with different immune gene markers. The copy number variation (CNV) of FCGR1A significantly influenced the abundance of immune infiltration in KIRC and SKCM. Conclusion: FCGR1A may be a potential prognostic biomarker and related to immune infiltration levels in diverse cancers, especially in CESC, CHOL, KIRC, and SKCM. Besides, FCGR1A may be involved in the activation, regulation or induction of immune cells.